Molecular Toxico-Pathology Responses Of EUDRILUS EUGENIAE TO 2- AMINO-l-METHYL-6-PHENYLIMIDAZO[4,5- bJPYRIDINE (PhIP) AND 2-AMINO-3,8- DIMETHYLIMIDAZO [4,5-f]QUINOXALINE (MeIQx) - Balogun, Wasiu Gbolahan (2019)
The carcinogenic risks of highly heated proteinaceous foods are at large associated with the formation of heterocyclic amines (HCAs), evidence in their substantial presence in the biota. The earthworm Eiidrilus eugeniae (E. eugeniae) is a terrestrial ubiquitous animal, susceptible to toxicity from environmental contamination, and a suitable model for understanding the mechanism of toxic agents such as HCAs. Thus, this study elucidated the vulnerability of E. eugeniae to HCAs induced toxicity using a modified OECD TG207 approach.